2011
DOI: 10.1002/jso.21947
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity, mortality, and pathological response in patients with gastric cancer preoperatively treated with chemotherapy or chemoradiotherapy

Abstract: Preoperative treatment with Ch or ChRT for locally advanced gastric cancer can be performed safely with an acceptable operative morbidity and low operative mortality rate with careful consideration of the added risk associated with BMI and surgical resection of the pancreas and spleen. Ch and ChRT is feasible and effective in terms of pathological response and R0 resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…The 30-day POM was 4.27%, and the in-hospital mortality to 90 days was 5.99%, comparing favorably with many studies, 1,7,15,16 especially because we conducted a multicenter study. The following factors on univariate analysis were related to POM: age, ASA score, tolerance of neoadjuvant chemotherapy, metastatic disease diagnosed preoperatively or perioperatively, and extended resection.…”
Section: Commentsupporting
confidence: 56%
“…The 30-day POM was 4.27%, and the in-hospital mortality to 90 days was 5.99%, comparing favorably with many studies, 1,7,15,16 especially because we conducted a multicenter study. The following factors on univariate analysis were related to POM: age, ASA score, tolerance of neoadjuvant chemotherapy, metastatic disease diagnosed preoperatively or perioperatively, and extended resection.…”
Section: Commentsupporting
confidence: 56%
“…Although many phase II trials have adopted pathRR as the primary endpoint, there is no globally accepted consensus regarding the optimal cutoff percentage to determine the responder. Various definitions regarding the cutoff percentage of residual tumors such as 10 % [7][8][9][10][11][12], 40 % [13], 50 % [9,14], or 67 % [15][16][17][18][19][20][21][22][23] have been used in previous clinical trials. According to the criteria proposed by Becker et al [24,25], 10 or 50 % is typically used as the cutoff percentage in Western countries, while 33 or 67 % is commonly used in Asian countries following the definition specified in the Japanese Classification of Gastric Carcinoma [26].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) is the second leading cause of cancer death worldwide after lung cancer in 2010, although mortality deaths have decreased slightly from 774,000 in 1990 to about 755,000 in 2010 [1],[2]. Epidemiological studies have showed that environmental factor, including diet, tobacco smoking, alcoholic consumptions and, especially, infection with Helicobacter pylori are associated with a higher risk for GC [3], [4].…”
Section: Introductionmentioning
confidence: 99%